The Best Smartphone Brand using The Preference Selection Index Method - Angriawan, Sherkhing; Dewi Nasien; M. Hasmil Adiya; Roni Sanjaya; Yenny Desnelita; Feri Candra (International Journal of Electrical, Energy and Power System Engineering, 2022)
The existence of the Covid-19 pandemic has had a tremendous impact in all aspects, including the educational aspect. Before the pandemic, education generally is done by face-to-face learning, but after the pandemic hit, it changed to online learning. Several problems often occur during online learning education, especially for college students, such as a mobile phone that does less support for online learning activities. Hence, the author wants to build an application that has the function of helping users to choose a mobile phone which supports online learning activities. The selection decision used by the author is the Preference Selection Index method since it can determine the value for each attribute and continue with a ranking that is able to select each attribute from the best alternative from several existing alternatives, with the help of a decision support system and application of the PSI (Preference Selection Index) method. The result indicates that the highest value obtained from smartphone selection with an average price under 3 million rupiah is infinix by 90.88%. The application's output meets the purpose because it is able to provide recommendations to buyers in determining which smartphone to buy and can simplify the decision-making process to become more accurate, effective, and efficient in generating information.